The Analysis of Impoliteness within Grammar Nazi Context in Twitter Tweets - Soehendro, Eunike Imanuela; Jumanto, Jumanto (Journal of Pragmatics Research, 2022)
This research focuses on one of the phenomena namely the Grammar Nazi phenomenon. In the present paper, the Grammar Nazi phenomenon was a phenomenon where people did not hesitate to criticize other people's grammatical errors. This phenomenon of Grammar Nazi was associated with the theory of Impoliteness Strategy by Culpeper (1996). This research is a qualitative one, where 100 data employed were processed first using a coding technique. The results obtained from this study are 55% of the data using the Bald on Record strategy, 18% of the data using the Sarcasm or Mock Politeness strategy, 16% of the data using the Negative Impoliteness strategy, 11% of the data using the Positive Impoliteness strategy, while 0% data using the Withhold Politeness strategy. It was also found that 61% of the data of the Grammar Nazi phenomenon used verbal bullying only to attack the face of authors of the posts, while the remaining 39% of the data used verbal bullying with intentions to correct grammatical errors, hence providing benefits for authors of the posts. The Grammar Nazi phenomenon also has a different impact on everyone. It can be seen from the characteristics of the utterances used by the Grammar Nazi.Keywords: Grammar Nazi, Grammar Nazi Phenomenon, Impoliteness Strategy, Five Strategies, Twitter.